Python Functions Video Course - Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2020)
Many people wrongly believe that to program properly in Python, it is necessary to master all of its many moving parts. But the single most important part of modern Python programming - the part you should learn first - is the function. What can you do with a function? Build command-line tools, web applications, GPU programming, serverless, distributed computing, and machine learning. In the cloud and machine learning era, the function rules. In this course, you'll begin your Python journey through learning about this critically important subset of the Python language. You'll master the use of functions much more quickly by not getting bogged down with all the rest.